Use of artificial intelligence in the marketing system: current trends and challenges - Adamyk, Viktoria; Ivanovskyi, Oleksandr (Herald of Economics, 2025)
Introduction. Artificial intelligence (AI) is radically changing the marketing sphere, automating processes, personalizing interaction with consumers and improving analytics. However, its implementation is accompanied by challenges, including ethical, legal and economic aspects. The study is aimed at analyzing current trends in the use of AI in marketing and assessing its effectiveness.The purpose of the study is to analyze current trends and strategies for using artificial intelligence in marketing activities.Resurch methods. The study used general scientific and special methods: a systematic approach, comparative analysis, SWOT analysis, elements of the case method and the results of the expert assessment method, which made it possible to assess the effectiveness of strategies for using AI in marketing, to identify its advantages, risks and challenges.Results. There is a clear trend in the world to increase the use of AI in all types of economic activity, including marketing. Businesses and organizations choose one of three marketing strategies – with integrated AI, with limited use of AI, or without it at all. Based on the analysis, it was found that since all strategies have both advantages and disadvantages, they can be effectively applied in marketing activities, as proven by numerous cases. The most balanced is the limited and controlled use of this technology, because such an approach allows you to maximize the benefits of AI while minimizing risks. However, this limitation does not allow you to fully realize the potential of AI, which can be a barrier to future innovations.